Analisis Perlakuan Akuntansi Bitcoin Dan Implikasinya Terhadap Keputusan Investasi Generasi Z Berdasarkan Standar Pelaporan Keuangan - Andrea Geovani (Jurnal Pajak dan Bisnis, 2026)
The rapid adoption of Bitcoin as a digital asset among Generation Z poses new challenges for financial reporting transparency and entity accountability. This study aims to analyze the influence of understanding financial reporting standards on Generation Z's investment decisions, with the perception of accounting treatment as a mediating variable. Using an explanatory quantitative approach, data were collected through structured questionnaires from 150 Generation Z respondents who own crypto assets and possess an understanding of financial statements. Data analysis was performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method via SmartPLS 3 software. The results indicate that the understanding of financial reporting standards has a positive and significant effect on investment decisions (O=0.234;p<0.05). The most crucial finding reveals that the perception of accounting treatment has a very dominant influence on investment decisions (O=0.719;p<0.001) and is significantly proven to mediate the relationship between the understanding of standards and investment decisions. This model exhibits very high predictive power, with an R2 value of 0.883 for the investment decision variable and a Q2 value of 0.643, indicating strong predictive relevance. These results imply that for young investors, the clarity of accounting regulations (such as recognition and fair value measurement) is not merely an administrative formality, but a primary trust signal in economic decision-making. This study recommends that regulators develop more adaptive and transparent digital asset reporting standards to enhance capital market efficiency in the digital era.